Methadone toxicity in a poisoning referral center - Fatemeh Taheri; Ahmad Yaraghi; Ali Mohammad Sabzghabaee; Maryam Moudi; Nastaran Eizadi-Mood; Farzad Gheshlaghi; Ziba Farajzadegan (Wolters Kluwer Medknow Publications, 2013)
Objective: Methadone poisoning can occur accidentally or intentionally for suicide or homicide purposes. The aim of this study was to evaluate the epidemiological and clinical manifestations of Methadone poisoning. Methods: A descriptive analytical study was performed from 2010 to 2012 in the poisoning emergency and clinical toxicology departments of Noor hospital affiliated with Isfahan University of Medical Sciences (Isfahan, Iran). All patients with Methadone poisoning within this period of time were investigated. Different variables were recorded in a checklist. Findings: A total of 385 patients were studied. About 85.7% had ingested only Methadone and 14.3% had ingested other medications with Methadone. Mean ± standard deviation of the age was 32.1 ± 15 years (range: 1-90). Most of the patients were male (76.4%). Nearly 40% of the patients were narcotic addicts, 25.5% were addicts under surveillance of Methadone maintenance therapy centers and 34.5% were non-addicts. Intentional poisoning was observed in most of the patients (57.7%). Most of the patients had a low level of consciousness on admission (58.2%). Respiratory depression and hypotension was observed in 35.6% and 12.7% of the cases as the most common symptoms. Regarding vital signs, there was a significant difference in respiratory rate on admission among different evaluated groups (P = 0.02). Length of hospital stay was 18.79 ± 0.72 h (range: 4-240 h, median: 15 h). About 57 patients (25.8%) from the intentionally poisoned patients and 19 patients (12.3%) from the unintentionally poisoned patients had a history of psychiatric disorder (P = 0.001). Most of the patients survived without complications. Conclusion: Addiction, age, gender, attempt to suicide and a history of psychiatric disorder were of the most important factors effective in Methadone poisoning, which should be considered in the public training and prevention of poisoning.